Relation of apolipoprotein E gene polymorphism with the severity of coronary artery disease in patients with stable ischemic heart disease - Seyda Yilmaz, Ahmet; Duman, Hakan; Citli, Senol; Gurbak, Ismail; Kahraman, Fatih (Annals of Medical Research, 2021)
Aim: Atherosclerosis begins from an early age and manifests in later years as Coronary artery disease (CAD). This inflammatory process is aggravated by age, smoking, hypercholesterolemia, hypertension, diabetes mellitus, and genetic factors. We aimed to investigate which isoform of APOE is related to extensive coronary lesions in patients with stable coronary heart disease.Materials and Methods: This study was carried on single center. One hundred and ten patients diagnosed with stable coronary artery disease by coronary angiogram were enrolled consecutively. Syntax score was calculated by a tool of website calculator (www.syntax.com). According to the Syntax score, patients were split into three groups. APOE genotyping was performed through blood samples. Patients split into three groups according to the APOE genotypes: E4 (3/4 and 4/4 genotypes), E3(3/3 genotype), E2 (2/2 and 2/3 genotypes). APOE groups were compared according to baseline characteristics and syntax scores.Results: Coronary angiography and APOE genotypes of 98 patients were analyzed. 81 of patients (%82.6) had E3E3 allele; 6 of patients (%6.1) had E2E3 allele; 10 patients (%10.2) had E3E4 allele and 1 patient (%1) had E2E4 allele. Due to the contrast effect of E2 and E4 on CAD, we excluded patients with E2E4 allele from the study. Firstly, we assessed distribution of APOE genotype E2 (E2E3), E3 (E3E3 and E3E4), E4 (E3E4) within 3 groups of syntax scores. Total of 6 patients of E2 allele was at low syntax score group. 83 patients of E3 allele were at the low-risk group of syntax score. 10 patients of E3 allele were at the mid group and 4 patients were at the high-risk group of syntax score. 7 patients of E4 allele subjects were at the low-risk and 1 patient was at the high-risk group of syntax score. Compared to syntax score groups and APOE genotypes, E2 alleles were in lower syntax score group versus E3 (P=0.046) and E4 (P=0.003) alleles. However E4 alleles were in higher syntax score group versus E3 alleles (P= 0.034). The Syntax score was seemed to be lower in the E2 allele group versus E4 and E2 groups (P=0.013).Conclusion: we reported the first study that E2 allele was related with less and E4 allele was more extensity and severity of CAD in patients with stable ischemic coronary disease.